Women's Involvement in Nagari Municipal Land Arrangement - Indraddin Indraddin; Kurnia Warman; Ardi Abbas; Retno Anggraini (Universitas Pendidikan Ganesha, 2024)
Women in Minangkabau culture are the heirs of traditional land, but in its arrangement and management, women are not significantly involved. At the level of implementing land registration, privately owned land has run smoothly, but problems often arise in managing customary land, both community customary land and Nagari customary land. This research aims to analyze women's involvement in managing Nagari traditional land. The research was conducted in Nagari Sungai Kamuyang, Limapuluh Kota Regency, using a qualitative approach. The analytical tool used is Anthony Ginddens' structural theory. The research results show that women's involvement in managing communal land is greater during consensus deliberation events. Women were more involved at the beginning of the activity, but men mostly carried out the implementation. In discussing the agreement to make Nagari Sungai Kamuyang a pilot project, women were invited to occupy the bundo kanduang position there as nagari officials. Women are no longer involved in determining boundaries in the field, and there is polarization in the division of labor between men and women. At the same time, discussions in forums ranged from socialization activities to building an agreement to make Nagari Sungai Kamuyang one of the pilot project locations for customary land management. The women present met and joined in the conversation. When a field assistance team was formed to determine land boundaries and land measurements by BPN, BPN was involved for a longer time.